Mixed-method approach to the evaluation of rework provisions within general contract conditions (Construction Economics and Building, 2023)
Rework in construction contracts is an interesting topic as it influences contractual claims and disputes. Changes in design, work scope, and construction turn into rework and affect the contract sum, the project completion date and project performance. Thus, clear responsibility to manage rework is essential for construction contracts. Contractual rework provisions are difficult to trace as they are written indirectly or in a complex context. A well-defined contract with clear responsibilities before the project commencement will safeguard the contract from unforeseen circumstances. In this study, the stipulated provisions related to the causes of rework are reviewed and analysed in New Zealand standard form of contract. The research uses a mixed quantitative and qualitative method for data collection and analysis. This paper collects a list of rework causes, assesses each rework cause in the general contract conditions, and explores relevant rework clauses of NZS3910 contract. The study revealed five significant causes of rework that have been addressed in the contract conditions. Further investigation into the reminder causes during contract negotiation enables contract parties to manage their obligations under rework events. Properly addressing the causes of rework in the contract conditions improves the overall project performance and reduces contractual claims and disputes.